Next-Gen intestinal parasite detection: Leveraging metataxonomics for improved diagnosis of intestinal protists and helminths - Katherine Bedoya-Urrego; Nicolas Rozo-Montoya; Ana L. Galván-Díaz; Gisela M. Garcia-Montoya; Juan F. Alzate (PLoS ONE, 2026)
Intestinal parasites continue to pose a significant public health burden in low- and middle-income countries and are increasingly recognized in developed regions. Traditional diagnostic methods, primarily based on microscopy, remain widely used despite limitations in sensitivity and taxonomic resolution. In this exploratory study, we applied a next-generation sequencing (NGS)-based metataxonomic approach, integrated with classical phylogenetic methods, to characterize intestinal parasites in rural Colombian populations. We compare its performance with conventional microscopy, focusing on both protist and geohelminth detection. Metataxonomics outperformed microscopy in detecting Strongyloides stercoralis and enabled precise species and subtype level assignment for Blastocystis and Entamoeba spp., revealing frequent mixed infections. Microscopy detected Trichuris trichiura , Giardia , Cyclospora , and Chilomastix more effectively, highlighting limitations of current primers and DNA extraction methods. Cystoisospora was only identified by NGS. These results demonstrate the utility of NGS-based metataxonomics for broad parasite detection while emphasizing areas for methodological improvement and providing a foundation for future, larger-scale studies.